The formation of ordered heterostructures during the intercalation of phosphonic acids into a layered double hydroxide. - Williams, G; Norquist, A; O'Hare, D (2003)
The intercalation reactions have been studied using in situ energy dispersive X-ray diffraction; ordered second stage heterostructures were observed as intermediate phases, which is almost unprecedented for rigid layer host materials.